2018
DOI: 10.1073/pnas.1803599115
|View full text |Cite
|
Sign up to set email alerts
|

Dirac semimetal in β -CuI without surface Fermi arcs

Abstract: Anomalous surface states with Fermi arcs are commonly considered to be a fingerprint of Dirac semimetals (DSMs). In contrast to Weyl semimetals, however, Fermi arcs of DSMs are not topologically protected. Using first-principles calculations, we predict that β-cuprous iodide (β-CuI) is a peculiar DSM whose surface states form closed Fermi pockets instead of Fermi arcs. In such a fermiological Dirac semimetal, the deformation mechanism from Fermi arcs to Fermi pockets stems from a large cubic term preserving al… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 43 publications
1
36
0
Order By: Relevance
“…Calculations of this system ( Fig. 8(a), [35]) also reveal a second type-I BDP and an anti-crossing gap formed along this same axis approximately 1 eV below E F . This latter pair of crossings can be understood as a consequence of the mechanism shown in Fig.…”
Section: Universality Of Kz Mediated Band Inversionsmentioning
confidence: 67%
See 2 more Smart Citations
“…Calculations of this system ( Fig. 8(a), [35]) also reveal a second type-I BDP and an anti-crossing gap formed along this same axis approximately 1 eV below E F . This latter pair of crossings can be understood as a consequence of the mechanism shown in Fig.…”
Section: Universality Of Kz Mediated Band Inversionsmentioning
confidence: 67%
“…For example, a recent DFT study into the bulk band structure of β-CuI (D 3d ) demonstrated the presence of a parity inverted band gap formed at Γ, as well as a type-I BDP at the Fermi level, formed along the Γ-Z direction [35]. Calculations of this system ( Fig.…”
Section: Universality Of Kz Mediated Band Inversionsmentioning
confidence: 94%
See 1 more Smart Citation
“…Band crossings with a nontrivial topological invariant, including Weyl, Dirac, and unconventional fermions, have been attracting enormous attention in condensed matter [1][2][3]. For Weyl and Dirac fermions [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], they were realized experimentally in topological semimetal materials and further classified into type-I and type-II classes [20]. Unconventional fermions, which contain three-, four-, six-, and eightfold degenerate points, have been exhaustively classified by space group symmetries in solid-state systems with spin-orbit coupling and time-reversal symmetry.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, 3D Dirac semimetals share topological features with Weyl semimetals, such as Fermi arcs 11 , 12 and chiral anomalies 13 , 14 . Moreover, 3D Dirac points can also exhibit exotic anomalous effects compared with Weyl points, such as spin-polarized surface states 15 , closed Fermi pockets 16 , 17 , and oscillating quantum spin Hall effect in quantum well structures 10 , 18 .…”
Section: Introductionmentioning
confidence: 99%